2008
DOI: 10.1080/17458080701883699
|View full text |Cite
|
Sign up to set email alerts
|

Gas fingerprinting using carbon nanotubes transistor arrays

Abstract: This paper deals with the fabrication of carbon nanotube field effect transistors (CNTFETs) for gas sensing applications. Such devices exploit the extremely sensitive change of the Schottky barrier heights between carbon nanotubes (CNTs) and drain/source metal electrodes: the gas adsorption creates an interfacial dipole that modifies the metal work function and so the band bending and the height of the Schottky barrier at the contacts. Our aim is to achieve the fingerprinting of a specific gas using a CNTFET b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…They used Pt, Pd and Au as metal electrodes where each metal creates an analyte-specific pattern and enables discriminative detection. In that context, Bondavali et al [26] discussed the working mechanism of CNT FETs that have different contact metals under the exposure of DiMethyl-Methyl-Phosphonate (DMMP). They attributed the change in the transfer characteristics to the interaction between the gas and the metal.…”
Section: Introductionmentioning
confidence: 99%
“…They used Pt, Pd and Au as metal electrodes where each metal creates an analyte-specific pattern and enables discriminative detection. In that context, Bondavali et al [26] discussed the working mechanism of CNT FETs that have different contact metals under the exposure of DiMethyl-Methyl-Phosphonate (DMMP). They attributed the change in the transfer characteristics to the interaction between the gas and the metal.…”
Section: Introductionmentioning
confidence: 99%
“…It was not observed in [10] because the inter-electrode distances used are larger than ours. The resistance measured when the inter-electrode distance is less than 10 μm [6] is mainly attributed to ballistic transport in metallic nanotubes [11].…”
Section: Drift and Stabilizationmentioning
confidence: 99%
“…This mechanism is consistent with the evolution of the resistivity upon exposure to an electron donor or acceptor gas, respectively NO 2 and NH 3 , and was confirmed by ab-initio calculations. On the other hand, Bondavalli et al interpret the response of CNT-based gas sensors by a different mechanism: a modification of the Schottky contact between the semiconducting nanotubes and the electrical contacts [6]. Using this approach, and varying the electrode metal, the authors reported a matrix of CNT-based gas sensors aiming at the analysis of complex atmospheres by recognition of different gas fingerprints.…”
Section: Introductionmentioning
confidence: 97%
“…This concept has been developed by a joint-research team of Thales and École polytechnique in France (Nanocarb Lab.) [20][21][22][23]. More precisely, they exploited the mechanism described by IBM researchers, the modulation of the metal work function operated by gas exposure, to get the fingerprinting of a particular gas using a large network of CNTFETs.…”
Section: Routes To Improve Selectivitymentioning
confidence: 99%